"I don't need to come out; I'm quite obvious": a qualitative exploration of the relationship between young black gay men and their heterosexual fathers in South Africa. Issue 1 (2nd January 2020) - Kekana, Putuke; Dietrich, Janan
ABSTRACT: This study explored the paternal relationship between young black gay men who have not disclosed their sexual orientation to their fathers and how their non-disclosure may possibly influence their relationship. A qualitative methodology grounded in a social constructionist paradigm was used. Six gay men were interviewed in Johannesburg, South Africa. Interviews were analysed using thematic analysis. The main finding was that the father–son relationship was reported to be poor during the participants' childhood but showed improvement in their adulthood. Given the South African context where paternal relationships are reported as difficult, the relationship was described as "normal". The findings show the definition of being gay to be socially constructed as someone who lacks masculine behaviour. Participants reported homophobic experiences in their childhood that may have influenced their paternal relationship. Participants did not disclose their sexual orientation because they perceived that their gender-nonconforming behaviour meant that their fathers already knew of their sexual orientation.